The share of the global energy mix: Signs of convergence?. (2nd March 2020) - Ghoshray, Atanu; Malki, Issam
Abstract: This paper investigates the convergence behaviour regarding the share of global energy mix, as measured by primary energy consumption. Recent studies that employ stationary tests of panel data suggest that such data support the convergence hypothesis; however, some drawbacks exist, as these studies rely on methods that do not necessarily imply a sufficient condition for convergence. This paper adopts the concept of relative convergence as proposed by Phillips and Sul (2007), which employs a time‐varying, idiosyncratic component. We choose to focus on various sources' global primary energy consumption and investigate the long‐ run dynamic behaviour by source. The key finding of this paper is that two distinct clubs of convergence of energy can be determined: renewable and non‐renewable energy clubs of convergence.